Edukasi Sadar Sampah dan Lingkungan dalam Rangka Pencegahan Penyebaran Covid-19 di Lokasi Wisata Ulee Lheue - Faradilla Fadlia; Nur Izzaty; Kana Puspita; Siti Nur Zalikha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Ulee Lheue Beach is one of the marine tourism sites in Banda Aceh. Its appearance, apart from attracting visitors to enjoy the beauty of the shore, also has consequences for piles of garbage thrown carelessly by the visitors to the shoreline which has an impact on environmental damage. In addition, the visitors tend to heed the government’s appeal to strictly commit to health protocols such as social distancing, gathering prohibition, and wearing masks while they visit the tourism spots. Therefore, this community outreach sought to map the knowledge of the tourists about waste and its impact on tourism sites and its relation to the dangers of Covid-19. This service employed mixed methods (quantitative and qualitative). The survey results showed that the visitors have fairly good knowledge regarding the dangers of waste and Covid-19 yet still uninternalized in their daily attitudes. Thus, the service team provides education through leaflets and videos on Youtube channels, hoping that the visitors would have higher commitment towards the environmental hygiene and health protocols at tourist sites.